Facile synthesis of cationic surfactant-treated hierarchical nanorods SnO2@CdO nanocomposite photocatalyst for degradation of methylene blue under sunlight. (2022) - Perumal, V.; Sabarinathan, A.; Robert, R.; Prabu, K.M.; Uthirakumar, R.
Abstract: CTAB-treated hierarchical nanorods cadmium oxide nanorods loaded tin oxide (SnO2 @CdO/CTAB) nanocomposite has been prepared by simple chemical co-precipitation technique. The X-ray diffraction pattern analysis revealed the as-prepared CTAB-treated nanocomposites possess tetragonal rutile structure having appreciable crystallinity with crystallite sizes in the range of 100–115 nm. The diffuse reflectance absorption spectrophotometer investigation confirms that the efficient absorption band of SnO2 @CdO/CTAB nanocomposites have red shift over the SnO2 . Fourier transform infrared spectroscopy (FTIR) investigation confirms the prepared SnO2 @CdO/CTAB nanocomposites encompass the characteristic bands of both SnO2 and CdO. The morphology of the prepared nanocomposites were performed by FESEM and shows that hierarchal nanorods structure. The EDX analyses revealed all the samples are composed of Sn and O elements. The photocatalytic performance of the prepared SnO2 @CdO/CTAB hierarchical nanorods nanocomposites was evaluated via methylene blue (MB) dye removal under direct natural sunlight irradiation.